Tinjauan Budaya Pidato Presiden Joko Widodo Pasca Vaksinasi Pertama di Indonesia - Emma Ratna Sari Moedy (Jurnal Ilmiah Cakrawarti, 2021)
This short speech when President Jokowi received the first vaccination gave birth to a large discourse regarding the involvement of all parties in one problem, regardless of racial and group interests. The interactions that occur touch the global realm because they are reported through media networks to the realm of small groups through social media applications. Interaction through the media reaches the old, young and millennial groups to prove that vaccination is only one way to ensure that everyone gets alternative health solutions during a pandemic in addition to the habits implemented in health protocols, namely washing hands, wearing masks and keeping your distance. Indonesia as the country with the largest Muslim population must ensure that the vaccines in circulation are halal- certified. Mental readiness is important to understand and implement through continuous and continuous mitigation or prevention. The community must understand and learn from disaster management in other countries.